Timepix detector as a tool for X-ray and gamma dosimetry. (December 2017) - Rubovič, Peter; Bergmann, Benedikt; Ekendahl, Daniela; Hůlka, Jiří; Judas, Libor; Kohout, Zdeněk; Pospíšil, Stanislav; Štekl, Ivan
Abstract: We present a concept of using Timepix detector for real-time and simultaneous measurements of various external dosimetry and operational quantities in X-ray/gamma fields with broad range of air kerma rates ranging from natural background levels to the order of Gy·h −1, including intensive pulsed sources used in medicine. Timepix is a hybrid semiconductor detector of ionizing radiation which can visualize tracks of particles interacting in the semiconductor pixelated sensor bump bonded to the Timepix readout chip. Energy deposited in the individual pixels and properties of these tracks enable us to classify the incident radiation and to assign the correct conversion coefficient between a number of detected events and the desired quantity, e.g. an ambient dose equivalent rate. This paper shows calibration measurements of such dosemeter and discusses its properties. Highlights: Concept of using Timepix detector as a real-time X-ray/gamma dosemeter. The tracks of ionizing particles are visualized in the detector. The composition of the tracks depends strongly on the incident spectrum. Measurements for air kerma rates from background levels to the order of Gy·h −1 . Possibility to use such detector with intensive pulsed sources when triggered.